ANALISA SIFAT MEKANIK DAN STRUKTUR MIKRO HASIL PENGELASAN GESEK PIPA STAINLESS STEEL AISI 304L - Muh Iswar; Abdul Salam; Aminuddin Aminuddin; Fahruddin Fahruddin (Politeknik Negeri Ujung Pandang, 2017)
Friction welding is a metal connection that occurs due to heat caused by pressure/friction force due to rotation of metal one to other metal axis. In addition, spindle shaft with this process can minimize the shift axis of the welded material. The purpose of this research is to know the effect of variation of rotation speed and wrought time on mechanical properties (tensile strength, flexural and hardness) and microstructure of AISI 304L Stainless Steel pipe of friction welding. The experiment was carried out by stages of friction welding process on Pindad type lathes by varying the rotation (550 rpm, 1020 rpm and 1800 rpm) and wrought time (25 seconds, 35 seconds, 45 seconds) using stopwatch. The axial force is obtained through a power screw mechanism on the tail-stock with a forging pressure of (Pu = 28.02 MPa). Welding temperature is 1050˚C. The friction welding results are then formed into specimens for mechanical testing of tensile test specimens and standard ISO 82-1974 (E) test, DP8 size and hardness test using the Rockwell method. The test result showed that the tensile strength of the friction welding result with the highest σ max value in 1800 rpm/45 second specimen was 446,22 N/mm2 decreased when compared with raw material that is 788,62 N/mm2. the bending strength of the friction welding result with the highest σ max value in the 1800 rpm / 45 second specimen is 1470 N / mm2 decreased when compared with the raw material ie 1950 N/mm2. The highest hardness value is located in the part of the welded joint of specimen with variation of 1800 rpm / 45 second rotation of 77,5 HRA decrease from hard raw material value is 81,0 HRA. Rotation variations affect the mechanical properties of the material, the higher the engine rotation the value of its strength increases. Similarly, if the wrought time longer then the value of strength will also increase. Observations on microstructure with the variation of rotation speed and time of wrought there is a noticeable change is in the weld metal there are many austenite so that the strength and hardness value almost closer to Raw material hardness value. As for the HAZ area that there are many ferrit so that the strength and hardness value close to hardness value Raw material.